PECULIARITIES OF PRO-OXIDANT AND ANTIOXIDANT HOMEOSTASIS IN PIGS DURING REPRODUCTIVE CYCLE - Usenko, S.O.; Shostia, A.M.; Polischuk, A.A.; Slynko, V.H.; Bondarenko, O.M.; Myronenko, O.I.; Bilash, S.M. (World of Medicine and Biology, 2019)
Experimental data of many scientists indicate the leading role of active form of oxygen in providing morbidity, survival value of sperm cells, maturation of ovum. After pregnancy, the maternal body is under the influence of oxidative stress, which may be accompanied by a destruction of the processes of placenta, fetal development and premature birth. It requires the development of antioxidant nutrition programs, based on a deep understanding of the mechanism and its specific action. The aim of the investigation was to establish the peculiarities of pro-oxidant homeostasis in pigs in different periods of sex cycle and pregnancy. 5 clinically healthy pigs aged 8 months of Myrhorod breed and with mass of 125-130 kg were involved in investigations. Blood test was done fasting in different periods of reproductive cycle: luteal phase, estrus, on the 15th, 20th, 30rd , 60th, 90th, 104th, 113rd days of pregnancy and in 12 hours after farrow. The condition of pro-oxidative homeostasis in blood was investigated by xanthine oxidase, concentration of diene conjugates, and content of TBA-reactive substances. The level of antioxidative protection by activity of superoxide anion scavenger, catalase activity, content of glutathione, ascorbic acid and dehydroascorbic acid, Vitamin A and concentration of vitamin E was evaluated. It has been indicated, that in pigs during estrus processes peroxide oxidation in blood are accelerated; activity of xanthine oxidase increases (р